Electrical and mechanical properties of surface functionalized carbon nanotubes incorporated graphite-phenolic composite bipolar plate for PEMFC - Chaiwan P. (2017)
© 2016 Trans Tech Publications. This research aims to study the effect of the functionalization of the multiwall carbon nanotubes (MWCNTs) on the mechanical property improvement of phenolic composites for bipolar plate applications in proton exchange membrane fuel cells (PEMFC). The MWCNTs were oxidized by strong acid and silanized by silane coupling agent in order to enhance the interfacial adhesion between the MWCNTs and matrix and were used as reinforcement in the phenolic composites. The silanized MWCNTs was found to improve the mechanical properties of the composites; however, they caused the decrease of electrical conductivity due to the wrapping of the MWCNTs with non-conductive silane molecules. Nevertheless, the conductivity of more than 100 S/cm is maintained to meet the DOE requirement of materials for use as bipolar plates.